PENGARUH TEKNIK DISKUSI TERHADAP SIKAP SOLIDARITAS PADA SISWA SMKN 4 MATARAM - Rohmatul Ummah; H. M. Syarafuddin (Universitas Pendidikan Mandalika, 2019)
Discussing is a guidance effort given to several individuals through group situations, with the target group being individuals who have the same problems so that students can help themselves in increasing their solidarity attitude. The formulation of the research problem is